The Diametrically Loaded Cylinder for the Study of Nanostructured Aluminum–Graphene and Aluminum–Alumina Nanocomposites Using Digital Image Correlation - Tabandeh-Khorshid, Meysam; Schultz, Benjamin F.; Rohatgi, Pradeep K.; Elhajjar, Rani (Frontiers in Materials, 2016)
Non-contact methods for characterization of metal matrix composites have the potential to accelerate the development and study of advanced composite materials. In this study, diametrical compression of small disk specimens was used to understand the mechanical properties of metal matrix micro and nano composites. Analysis was performed using an inverse method that couples digital image correlation and the analytical closed form formulation. This technique was capable of extracting the tension and compression modulus values in the metal matrix nanocomposite disk specimens. Specimens of aluminum and aluminum reinforced with either Al2O3 nanoparticles or graphene nanoplatelets (GNP) were synthesized using a powder metallurgy approach that involved room temperature milling in ethanol, and low temperature drying followed by single action compaction. The elastic and failure properties of MMNC materials prepared using the procedure above are presented.